Comparing and Contrasting the Samurai Gintoki and Hijikata Personalities from Gintama - Leonardo Kevin Martono (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
The mask or persona will be discussed in the first subchapter. Gintoki and Hijikata both have a mask that they wear to show to other people or society. Gintoki's persona is lazy, childish, and cowardly since his motivation is to live a carefree life, free of obligations, and to project an image that others will not hold high expectations of him. Behind every façade is their genuine personality, which they prefer not to project. The shadow will be discussed in the second subchapter. Their repressed feelings and flaws are contained in the shadow. I will also go through how each character's shadow works. Gintoki's shadow is his guilt about killing his own teacher as a result of being forced to make some difficult decisions. Whereas Hijikata’s shadow is regret of being unable to save his brother. The findings are that a human psyche is complex, and each has his different causes and outcomes.Keywords: samurai, persona, shadow, anima, animus, personality